Zombie boys Vol 2 - Pak, Greg; Jackson, Dan, 1971-; Favoccia, Valeria; Piekos, Nate; Chan, Ron (Minneapolis, Minnesota Spotlight, a Division of ABDO, 2022)
Mike, Lucas, Dustin, and Will each prepare to shoot their extra credit zombie movie with new kid Joey Kim.
"Published by agreement with Dark Horse Comics"--Title page verso.
"Dark Horse Books."
"Netflix official merchandise"--Title page verso.
Based on the television program Stranger things.
113082
Keywords: Friendship -- Comic books, strips, etc. -- Fiction; Motion pictures -- Production and direction -- Comic books, strips, etc. -- Fiction; Video recordings -- Comic books, strips, etc. -- Fiction; Horror films -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; Paranormal fiction; Video recordings; Comics (Graphic works); Horror comics; Paranormal comics; Science fiction comics